Addressing lower-priced cigarette products through three-pronged comprehensive regulation on excise taxes, minimum price policies and restrictions on price promotions. Issue 2 (3rd March 2022) - Ribisl, Kurt M; Golden, Shelley Diane; Huang, Jidong; Scollo, Michelle
Abstract : The prices that smokers pay out-of-pocket for their tobacco products ultimately influence their smoking behaviour. Although cigarette excise taxes are arguably the best and most used policy to increase cigarette prices, taxes are only one component of retail cigarette prices. The persistence of lower-priced products, disproportionately purchased by lower-income smokers, in jurisdictions with high excise taxes is an Achilles heel for tobacco tax policy. When governments raise excise taxes, the tobacco industry responds. The industry reduces tax pass-through to minimise the price increases for lower-priced brands and offers price discounts to retailers and coupons to consumers. In addition, smokers who do not quit after tax increases may downshift brands, purchase in bulk or substitute lower-priced tobacco product types. This may be particularly true for price-sensitive smokers, including those with lower incomes. We propose that raising excise taxes will be more effective in reducing the persistence of lower-priced products and income-based smoking disparities when taxes are designed to raise prices frequently and substantially for all products and are combined with (a) minimum price laws and (b) bans on coupons, discounts and other promotions. In combination, these three complementary policies restrict the tobacco industry's ability to undermine the impact of higher excise taxes upon consumer prices. Very few jurisdictions have implemented comprehensive three-pronged tobacco price regulation, but doing so would likely address many of the limitations that come with a sole focus on raising excise taxes.